Determination of trihalomethanes in raw and treated water supply to a local city in Zimbabwe - Guyo, Upenyu; Moyo, Mambo; Nyamunda, Benias; Shumba, Munyaradzi; Chigondo, Fidelis (Seventh Sense Research Group Journal, 2016)
Concentration levels of trihalomethanes in raw and treated water for the city of Gweru were determined by solvent extraction followed by gas chromatograph detection. The trihalomethanes found were chloroform, dichlorobromomethane, dibromochloromethane and bromoform. Chloroform was the most abundant trihalomethane with concentration levels ranging from 3.70 ?g/L to 45.89?g/L. The concentration levels of trihalomethanes increased with increasing distance from the chlorination point . Total trihalomethane concentration in raw water ranged from nondetectable levels to 18.13?g/L and in treated water ranged from 6.83?g/L to 145.50 ?g/L. A slight increase in concentration levels of trihalomethanes was shown in warmer months with the highest concentration level of 145.80 ?g/L being recorded in September. Generally, the concentration levels obtained were lower than the maximum permissible limits of 460?g/L set by World Health Organisation (WHO).